Rethinking Arts Education in the Digital Era: A Narrative Review - Nazaruddin, M. Arief; Mahfudzi, Aan (Indonesian Scientific Publication, 2025)
This study provides a narrative review of digital transformation in arts education, with a focus on pedagogical models, curriculum innovation, technological integration, and global perspectives. The review draws on literature from databases including Scopus, Web of Science, Google Scholar, and PubMed, using keyword combinations related to digital transformation, pedagogy, and arts education. Inclusion criteria emphasized peer-reviewed studies published between 2015 and 2025, spanning diverse research designs. The findings indicate that project-based and STEAM learning approaches, combined with digital tools such as artificial intelligence and augmented reality, significantly improve student engagement, creativity, and adaptability. Curriculum reforms incorporating e-learning, blended, mobile, and ubiquitous learning models demonstrate how institutions globally are redesigning education to meet digital challenges. At the same time, systemic barriers—including insufficient infrastructure, limited teacher training, and policy gaps—continue to hinder effective implementation, particularly in developing countries. Comparative analyses highlight stark disparities between developed and developing contexts but also reveal innovative practices emerging from resource-constrained environments. The discussion emphasizes the importance of inclusive policies, sustained professional development, and international collaboration in addressing these barriers. Future research is needed to provide longitudinal evidence of the long-term impact of digital integration on creativity and professional readiness. The review concludes that digital technologies, when strategically integrated, are not supplementary but foundational to the future of arts education.